Childhood poisoning in Warri, Niger Delta, Nigeria: A ten year retrospective study - Gilbert IM. Ugwu; Blessing O. Okperi; Eunice N. Ugwu; Nekwu E. Okolugbo (AOSIS, 2012)
Background: Childhood poisoning is a common but avoidable problem in developingcountries such as Nigeria.Objectives: To determine the pattern of childhood poisoning in the Warri Niger Delta Regionof Nigeria.Method: The case notes of all the children seen at Central Hospital Warri, the reference basefor the region and GN Children Clinic the pioneer children's hospital in the region. This isa review of cases over a ten year period, from 2000 to 2009. The information obtained wasanalysed.Results: A total of 156 children aged 0-16 years diagnosed with poisoning were seen at thecentral hospital in Warri and at the GN Children's Clinic which is also in Warri over a 10year period from 2000 to 2009 under review. The male to female ratio is 2:1, and 75% of thechildren were aged 5 years or less. Most of the patients were from the low socio-economicclass. Most of the poisoning was unintentional and occurred through ingestion (97.6%).Kerosene was the major substance leading to poisoning (56.6%). Alcohol ranked second inthe study. Poisoning from drugs was the third most common source of poisoning and inthat category most of the indices were in the highest income group. Most of the patientspresented with mild symptoms and the mortality rate was 7%.Conclusion: Kerosine was found to be the most common source of poisoning. Most of thepoisoning was unintensional and deaths cause by this form of poisoning can be preventedwith proper health education and effective enactment of laws that will reduce the incidenceof childhood poisoning.